2005
DOI: 10.2174/1568007053544156
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Trapping as a Therapeutic Approach to Neuroprotection in Stroke: Experimental and Clinical Studies with NXY-059 and Free Radical Scavengers

Abstract: There is substantial experimental evidence that free radicals are produced in the brain during ischemia, during reperfusion and during intracranial hemorrhage. Removal of pathologically produced free radicals is therefore a viable approach to neuroprotection. Four compounds with free radical scavenging activity (tirilazad, ebselen, edaravone) or free radical trapping properties (NXY-059) have been examined in experimental models of stroke and evaluated clinically as neuroprotective agents. Both experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 72 publications
2
73
0
Order By: Relevance
“…In this line, the seleno-organic compound ebselen, which was originally developed as an anti-inflammatory agent, has been shown to protect against damage caused by free radicals in the CNS (Pérez-Ortiz et al, 2004;Green and Ashwood, 2005;Funchal et al, 2006;Gabryel and Ma1ecki, 2006;Ghisleni et al, 2008). However, in spite of the positive effects of ebselen, certain signs were observed in response to selenium-containing compounds that could be the basis of potential damaging actions.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, the seleno-organic compound ebselen, which was originally developed as an anti-inflammatory agent, has been shown to protect against damage caused by free radicals in the CNS (Pérez-Ortiz et al, 2004;Green and Ashwood, 2005;Funchal et al, 2006;Gabryel and Ma1ecki, 2006;Ghisleni et al, 2008). However, in spite of the positive effects of ebselen, certain signs were observed in response to selenium-containing compounds that could be the basis of potential damaging actions.…”
Section: Discussionmentioning
confidence: 99%
“…This may change if efficacy is observed with compounds currently in clinical trial for stroke, e.g., Cerovive (NXY-059). 45 The failure of many antiexcitotoxic compounds in clinical trials was a setback to the whole field of neuroprotection research. However, with the progress in understanding the physiological, anatomical, cellular, biochemical, and molecular basis of Alzheimer's disease and Parkinson's disease, disease-modifying therapies are now a realistic prospect.…”
Section: Drugs For Neurodegenerative Disordersmentioning
confidence: 99%
“…Various neuroprotective antioxidants of diverse structures and activities also display a biphasic dose-response relationship and afford less neuroprotection at higher doses than at lower doses. Examples include ebselen in a permanent MCAO model (Green and Ashwood 2005); triliazad mesylate in cultured retina cells (Levin, Clark et al 1996); dipyrimadole, vitamin E and N-acetyl cysteine in cultured hippocampal neurons (Farinelli, Greene et al 1998); and α-phenyl butyl nitrone (PBN), azulenyl nitrone (AZN), dimethylthiourea (Castagne, Lefevre et al 1999), and BXT-51072, a glutathione peroxidase mimetic (Castagne and Clarke 2000), in axotomized retinal ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…The successful translation of antioxidant therapy from animal models to the clinic, however, is not always straightforward (Committee. 2000;Green and Ashwood 2005). For example, although free radicals and oxidative stress are implicated in most human diseases, a recent meta-analysis of antioxidant supplements, such as vitamin E, vitamin A and β-carotene, found that antioxidant therapy did not confer benefit, but rather increased all-cause mortality in a variety of pathologies including neurological, cardiovascular, ocular, renal, endocrinological, gastrointestinal and dermatological diseases (Bjelakovic, Nikolova et al 2007).…”
Section: Introductionmentioning
confidence: 99%